Pelatihan Modul Ajar Berbasis STEAM - Andika, Windi; Sumarni, Sri; Syafdaningsih, Syafdaningsih; Utami, Febriyanti; Akbari, Akbari; Siregar, Rina Rahayu; Astika, Ruri Tria; Carisa, Aulia; Angraini, Melisa Nabima (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2024)
Background: The socialization of the Free Curriculum Implementation Program (IKM), especially the creation of STEAM-based teaching modules for Kindergarten (TK) Teachers in Lahat Regency, has not yet been widely implemented. Additionally, the educational background linearities of preschool teachers are low. On the other hand, Lahat Regency has collaborated with Sriwijaya University to minimize the existing gap. Based on the needs analysis, Lahat needs competent preschool teachers, especially in creating STEAM-based teaching modules for 4-6 aged children. Training and mentoring preschool teachers in creating STEAM-based teaching modules has involved 20 preschool teachers in Lahat, South Sumatra. Method: The activity flow includes 1) Planning, 2) Implementation, and 3) Evaluation. Inferential quantitative data analysis was conducted using the average percentage from pre-test and post-test scores of a 20-question instrument indicating STEAM-based teaching module components. Results: Based on the average pre-test score of 49% and the average post-test score of 71%, showed an increase of 23%. Additionally, preschool teachers were assisted in creating STEAM-based teaching modules and received group advice from the trainer. Some strengths and weaknesses include teachers being able to develop teaching modules according to the format, alignment with the developmental level of children, suitability of media, and evaluation. However, for STEAM-based activities formulated by teachers, further assistance is needed as some teachers are mistaken in designing activities suitable for the Technology and Engineering fields. Conclusion: The STEAM-based teaching module training received positive responses, was effectively implemented, and provided new knowledge for preschool teachers.